Tsukuru’s Social Actions Portrayed in Colorless Tsukuru Tazaki and His Years of Pilgrimage - Muttaqin, Prianto Nofan (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This study aimed to describe the social action types of Tsukuru Tazaki in the novel Colorless Tsukuru Tazaki and His Years of Pilgrimage by Haruki Murakami according to Weber’s social action theory (1978). Precisely, the object of the study was Tsukuru Tazaki's life and activities. The study's object was analyzed using the sociology of literature approach, which focused on literary works. This study used the literary criticism method. The researcher read, wrote, and identified the data in the form of content quotations provided through conversations and quotations that described the social action types. The results of the study revealed four types of social action. The first type was instrumentally rational action, which could be seen in Tsukuru’s way of maintaining harmonious relationships through community activities. The second type of social action was value-rational action, where Tsukuru used relationship values and the value of manners to keep his connection with his friends and other people. The third type was effective action when Tsukuru was encouraged by his emotional feelings to interact with others, such as jealousy, anxiety, fear, and love. The fourth type of social action was traditional action. The results of the type of social action showed that Tsukuru used his habituation to prepare himself for facing society and keeping in touch with his friends and family. In addition, the result also showed that value-rational action played a significant role in how Tsukuru's achieved his life goal, which was keeping his relationship with his closest people.